Fiber To The Home (Ftth) Network Infrastructure Design Using Gigabyte Passive Optical Network (Gpon) Technology South Solok District - Valentino, Riski; Yolanda, Amelia; Maria, Popy (PERFECT: Journal of Smart Algorithms, 2024)
Fiber To The Home (FTTH) Network with Gigabit Passive Optical Network (GPON) Technology in South Solok Regency, supervised by Ibu Amelia Yolanda, ST as supervisor 1 and Ibuk Popy Maria, ST STT as supervisor 2. Development of Telecommunications technology as a necessity Currently, communication has developed rapidly, transmission media facilities are needed that are capable of transmitting information with large capacities and adequate data transfer speeds. By implementing GPON technology, FTTH services can reach users at up to speed. This research aims to design an FTTH network using GPON technology in the South Solok Regency area, obtain results of identification and analysis of communication network needs for the Nagari Lubuk Gadang Selatan community in South Solok Regency, obtain results of FTTH network infrastructure design using GPON technology for Nagari Lubuk Gadang Selatan Regency. South Solok.